Beyond Cultural Heritage: Local Culture As A Social Mechanism For Interfaith Coexistence In Mataraman Society - Rosidah, Feryani Umi; Khoiroh , Himmatul; Maharani, Adinda; Tohari, Maula Safira (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2026)
This research examines the practice of culturally based interfaith coexistence in the Mataraman community in East Java. This study is motivated by the reality of religious diversity in Indonesia, this research focuses on the role of culture in interfaith coexistence in Mataraman, using qualitative methods from sociological and anthropological perspectives. Data collection techniques include interviews, observation, and documentation. Data analysis uses the Miles and Haberman model, namely data reduction, conclusion drawing, and data presentation. The results indicate that the local wisdom of the Mataraman community plays a significant role in building harmonious interfaith coexistence. Cultural values such as cooperation (gotong royong), tepo sliro (community service), and local traditions of village cleanliness, wayang (wayang), jamasan (traditional prayer), and jaranan (traditional Javanese dance) serve as a medium for a "dialogue of life." This enables interfaith interactions to take place inclusively and sustainably. From a symbolic perspective, these cultural practices function as systems of meaning that shape collective consciousness and strengthen social cohesion. Furthermore, cultural symbols such as the "Masgapur" (mosque, gate, and temple) road represent social integration rooted in tolerance and respect for diversity. The findings of this study reinforce and expand Hans Küng's theory of Global Ethics. While Küng emphasizes the importance of universal values such as humanity, solidarity, tolerance, and respect for others as the foundation of interfaith peace, this study shows that these values in Mataraman society are not built through theological debate, but rather are realized through local cultural practices such as cooperation, tepo seliro, wayang, and various shared traditions. Local culture serves as a medium for the actualization of global ethics that transform religious differences into social solidarity and sustainable harmony.